PERSEPSI GURU TERHADAP PELAKSANAAN FUNGSI KEPEMIMPINAN KEPALA SEKOLAH MENENGAH KEJURUAN NEGERI 1 PAINAN - Dori Yulia Putri (Jurnal Bahana Manajemen Pendidikan, 2014)
The purpose of this study is to see information about teachers' perceptions of the implementation of school leadership functions. The population is 91 teachers and 41 teacher sample is taken proportional random sampling. This research instrument is a question with a Likert scale models that have been tested for validity and reliability. Data were analyzed using the average value and the level of performance. The results of this research his the perception of teachers on the implementation of principal leadership functions in SMKN 1 Painan stay in pretty good category. Keywords: Function implementation of school leadership